Vaginal Mesh Removal Outcomes: Eight Years of Experience at an Academic Hospital. Issue 6 (November 2017) - Cardenas-Trowers, Olivia O.; Malekzadeh, Pouran; Nix, David E.; Hatch, Kenneth D.
Abstract : Objectives: The purpose of this study is to describe the clinical history leading up to and the outcomes after vaginal mesh removal surgery at an academic hospital. Methods: A retrospective case series of patients who underwent vaginal mesh removal from 2008 to 2015 was conducted. Demographics, clinical history, physical examination, pre- and postoperative symptoms, and number and type of reoperations were abstracted. Results: Between February 2008 and November 2015, 83 patients underwent vaginal mesh removal surgery at our hospital. The median time interval from initial mesh placement to removal was 58 months (range, 0.4–154 months). The most common preoperative symptoms were vaginal pain (n = 52, 62%), dyspareunia (n = 46, 55%), and pelvic pain (n = 42, 50%). Intraoperative complications were infrequent (n = 3, 4%). Of patients presenting for follow-up within 4 to 6 weeks postoperatively, the most common symptoms were urinary incontinence (n = 15, 28%), vaginal pain (n = 7, 13%), buttock pain (n = 5, 9%), and urinary tract infection (n = 5, 9%). There were no identifiable risk factors to predict which patients would have persistent postoperative symptoms or who would require more than 1 mesh removal surgery. After vaginal mesh removal, 29 patients (35%) required 1 or more reoperations, with 3 being the highest number of reoperations per patient. The total number of reoperations was 43, with a total of 63 individual procedures performed. Forty-four percent (n = 28) of the procedures were graft removals, 40% (n = 25) were pelvic organ prolapse surgeries (only native tissue repairs), and 16% (n = 10) were stress incontinence surgeries. More than 1 procedure was performed in 49% (n = 21) of the reoperations. Conclusions: Vaginal mesh removal surgery is safe; however, some patients require more than 1 procedure, and the risk factors for reoperations are unclear. Abstract : A retrospective case series that further demonstrates that vaginal mesh removal surgery is safe; however, some patients require more than one procedure and the risk factors for reoperations are unclear.